Association Between MTHFR Polymorphisms and the Risk of Essential Hypertension: An Updated Meta-analysis - Meng, Hao; Huang, Shaoyan; Yang, Yali; He, Xiaofeng; Fei, Liping; Xing, Yuping (Frontiers in Genetics, 2021)
Background: Since the 1990s, there have been a lot of research on single nucleotide polymorphism (SNP) and different diseases, including many studies on 5,10-methylenetetrahydrofolate reductase (MTHFR) polymorphism and essential hypertension (EH). Nevertheless, their conclusions were controversial. So far, six previous meta-analyses discussed the internal relationship between the MTHFR polymorphism and EH, respectively. However, they did not evaluate the credibility of the positive associations. To build on previous meta-analyses, we updated the literature by including previously included papers as well as nine new articles, improved the inclusion criteria by also considering the quality of the papers and applied new statistical techniques to assess the observed associations. Objectives: To explore the degree of risk correlation between two MTHFR polymorphisms and EH. Methods: PubMed, EMBASE, the Cochrane Library, CNKI and Wan Fang electronic databases were searched to identify relevant studies. We evaluated the relation between the MTHFR C677T (rs1801133) and A1298C (rs1801131) polymorphisms and EH by calculating the odds ratios (OR) as well as 95% confidence intervals (CI). Here we used subgroup analysis, sensitivity analysis, cumulative meta-analysis, assessment of publication bias, meta-regression meta, false-positive report probability (FPRP), bayesian false discovery probability (BFDP) and Venice criterion. Results: Overall, harboring the variant of MTHFR C677T was associated with an increased risk of EH in the overall populations, East Asians, Southeast Asians, South Asians, Caucasians/Europe and Africans. After sensitivity analysis, positive results were found only in the overall population (TT vs. CC; TT+ TC vs. CC; T vs. C) and Asian population (TC vs. CC; TT+ TC vs. CC; T vs. C). However, after further statistical assessment by FPRP, BFDF and Venice criteria, the positive associations reported here could be deemed to be false-positives and present only weak evidence for a causal relationship. In addition, when we performed pooled analysis and sensitivity analysis on MTHFR A1298C, all the results were negative. Conclusion: The positive relationships between MTHFR C677T and A1298C polymorphisms with the susceptibility to present with hypertension were not robust enough to withstand statistical interrogation by FPRP, BFDF and Venice criteria therefore these SNPs are probably not important in EH etiology